PENGARUH PUBLIC OWNERSHIP DAN GROWTH OPTION TERHADAP KINERJA KEBERLANJUTAN DENGAN INVESTMENT OPPORTUNITY SET SEBAGAI VARIABEL MODERASI - Endang Ruhiyat; Holiawati Holiawati (Universitas Pamulang, 2020)
This study aims to determine the effect of public ownership and growth options on sustainability performance with an investment opportunity set as a moderating variable. This type of research is associative quantitative using secondary data taken from the IDX website. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange from 2013 to the end of 2017. The sample selection procedure in this study is using purposive sampling method, only 50 company data that meet the criteria. The results of this study have a significant effect on Public Ownership Sustainability Performance, the influence of growth options on sustainability performance. Opportunity Set is able to moderate the influence of Public Ownership on Sustainability Performance. The Investment Opportunity Set does not moderate the effect of Growth Options on Sustainability Performance.